Lymphocytosis as a response biomarker of natalizumab therapeutic efficacy in multiple sclerosis. (June 2016) - Signoriello, E; Lanzillo, R; Brescia Morra, V; Di Iorio, G; Fratta, M; Carotenuto, A; Lus, G
Background: Natalizumab is an effective therapy in relapsing–remitting multiple sclerosis (RRMS), as it reduces lymphocyte transmigration through the blood–brain barrier (BBB) and induces lymphocytosis. Objectives: To analyse natalizumab-induced lymphocytosis (NIL) as a biomarker of drug efficacy. Materials and methods: We enrolled 50 relapsing–remitting (RR) and progressive–relapsing (PR) natalizumab-treated patients who had received at least 16 infusions and had been tested for lymphocyte count 24 hours before each administration. Clinical, MRI and hematological data were collected. Patients were divided into responders and sub-optimal responders according to the experience of at least one clinical and/or instrumental relapse during the treatment. Results: In 15 (30%) patients, an instrumental/clinical (14) or only instrumental (one) relapse occurred. We found a statistically significant difference in the mean percentage of the lymphocytes between the two groups over the first ten administrations ( p =0.04). The comparison between the time-to-relapse in the groups with high and low levels of lymphocytes showed that the group with a low NIL had a greater risk of relapse ( p =0.03). Conclusions: We suggest that NIL could be a biomarker of therapeutic efficacy in patients with RRMS treated with natalizumab, and that the risk of relapse may be higher in patients with a lower-than-expected NIL.